Electronic-reconstruction-enhanced hydrogen evolution catalysis in oxide polymorphs - Yangyang Li (Nature Portfolio, 2019)
Converting solar energy to hydrogen fuel requires light-absorbers that well-match the wavelengths of incoming sunlight. Here, authors prepare a broadband visible-light-absorbing molecular complex that efficiently produces hydrogen from water.